Bacterial interactions with platelets: defining key themes - Alfar, Hammodah R.; Whiteheart, Sidney W. (Frontiers in Immunology, 2025)
As first responders to vascular injury and microbial invasion, platelets play a critical role in hemostasis and immunity. Previous reviews have explored how different platelet receptors can be activated by various bacterial proteins, yet strain-specific perspectives remain underexplored. In this review, we highlight eight bacterial strains that have been associated with thrombosis, each possessing unique proteins or toxins capable of activating or modulating platelets. We discuss some common themes in the molecular interactions between these bacterial components and their effects on platelet function. Some interactions influence platelet aggregation, granule secretion, pro-inflammatory cytokine release, and thrombo-inflammatory responses, while others only mediate bacterial survival. By focusing on strain-specific mechanisms, this review provides an understanding of the different strategies employed by bacteria to manipulate platelet functions. These insights may aid in developing targeted therapeutic interventions to mitigate platelet-associated complications during bacterial infections.